Plasmid Profiles and Prevalence of Intermediately Virulent Rhodococcus equi from Pigs in Nakhonpathom Province, Thailand: Identification of a New Variant of the 70-kb Virulence Plasmid, Type 18 - Chaithep Poolkhet; Suksun Chumsing; Worawidh Wajjwalku; Chihiro Minato; Yukiko Otsu; Shinji Takai (Veterinary Medicine International)
The prevalence of intermediately virulent Rhodococcus equi isolates from pig submaxillary lymph nodes from four slaughterhouses in Nakhonpathom province, Thailand, was investigated. The isolates were tested for the presence of virulence plasmids and the 20-kDa virulence-associated protein antigen (VapB) gene by PCR. Of the 734 submaxillary lymph nodes tested, 19 (2.6%) produced positive cultures of R. equi. All 19 isolates were positive for the VapB gene and contained virulence plasmids that were identified as type 1 (six isolates), type 6 (two isolates), type 7 (one isolate), type 16 (two isolates), and a new variant (eight isolates). Based on the restriction digestion patterns of the plasmid DNAs, we tentatively designated the variant as type 18. Investigation of the prevalence and plasmid profiles of VapB-positive R. equi in pigs should be extended throughout Thailand to evaluate potential sources of zoonotic infections.